Presentation and Management of Malignant Tumors of Thyroid Gland in ESW Mayo Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Objective: To review the cases of malignant tumors of thyroid gland in respect to their presentations, histological types and its management.Materials and Methods: A total of 194 cases of malignant tumors of thyroid gland operated from 2006 to 2013 in East Surgical ward, Mayo hospital , Lahore are reviewed. The distribution of histological types, presenting symptoms and outcome of treatment are discussed.Results: Out of 194 cases, 71.1% were females and 28.9% were males. 88.6% were euthyroid, 9.2% were hypothyroid and 2% were hyperthyroid. 40.2% presented with a solitary nodule, 58.5% with multinodular goiter and 31.9% with goiter along with cervical lymphadenopathy. 3.6% had hoarseness and fixed unilateral vocal cords. 87.6% were primary tumors and 12.3% were recurrent tumors. 64.3% were Papillary carcinoma, 30.3% were Follicular carcinoma, 3.7% were anaplastic carcinoma and 3.2% were medullary carcinoma. 31.4% underwent lobectomy and isthmusectomy followed by completion thyroidectomy, 27.8% had total thyroidectomy, 29.3% had total thyroidectomy and unilateral block neck dissection, 5.1% had total thyroidectomy and bilateral block neck dissection, 2% had subtotal thyroidectomy, 0.05 % had isthmusectomy, 1.03% had Sistrunk’s operation followed by total thyroidectomy and 0.05% had suprahyoid neck dissection.Conclusion: Female preponderance was found in our study in carcinoma thyroid. Papillary carcinoma was the commonest cancer type found followed by Follicular carcinoma. Both commonest types of cancers if treated in time and adequately can result in good patient’s survival.